Characteristics of farmers and marketing strategies of citrus fruits west miomaffo district - Lambertus Nesi Bria; Maria Xaveria Bai; Maria Nelde Soi; Boanerges Putra Sipayung; Achmad Subchiandi Maulana (Agriekonomika, 2024)
The main obstacles in citrus fruit farming in West Miomaffo District are education, farmer experience, age, marketing aspects are factors in the problem of decreasing production and farmer income. The purpose of the study is a marketing strategy for citrus fruits through a characteristic approach of farmers. Data collection in the form of primary, secondary data and FGD methods. The analysis was carried out in a qualitative descriptive manner. The results showed (1) the characteristics of male farmers had a percentage of 56%, age 35%, family dependents 59%, elementary school education level of 60%, farming experience of 34%, and land area of 56%. (2) citrus fruit marketing strategies; 1) products consist of, product range, quality, and size; 2) price; price lists, discounts, payment periods and immediate terms; 3) promotions; sales promotion, public relations, and direct marketing; 4) premises; channels, coverage, location, and transportation. The conclusion of the research is that by increasing farmer education and expanding land area, it can improve quality, size, price, expand marketing channels and have a wider scope of marketing locations.